Utility of Aminotransferase/Platelet Ratio Index to Predict Liver Fibrosis in Intestinal Failure–Associated Liver Disease in Pediatric Patients - Rumbo, Carolina (2016)
BACKGROUND: Intestinal failure-associated liver disease (IFALD) is a frequent indication for intestinal transplantation. Liver biopsy (LBX) is the gold standard test for its diagnosis. Identifying noninvasive markers of fibrosis progression would be of considerable clinical use. Aspartate aminotransferase/platelet ratio index (APRI) has a good correlation in adult patients with chronic liver disease; few studies have been performed in children with IFALD.AIM:To evaluate APRI in a cohort of children with IFALD. MATERIALS AND METHODS: Retrospective analysis of a prospective database of patients <18 years with severe intestinal failure and at least 1 LBX, registered in our unit from March 2006 to December 2014. RESULTS: Forty-nine LBX were done on 36 patients: 20 were male, and 31 had short gut. Fibrosis was found in 71% of LBX. Biopsies were grouped according to the fibrosis stage (METAVIR [M]): (1) group 1 (G1) LBX with M 0, 1, 2 (n = 33) and (2) group 2 (G2) LBX with M 3, 4 (n = 16). The median APRI score was 0.92 (interquartile range [IQR] 0.63-1.50) for G1 and 2.50 (IQR 1.81-5.82) for G2 (P = .001) The c statistic of the receiving operating characteristic curve was 0.79 (95% CI 0.64-0.94; P < .001). The analyses allowed identifying a cutoff value for APRI of 1.6 as the point with the best sensitivity (81%) and specificity (76%) to predict advanced fibrosis. CONCLUSIONS: APRI in this cohort of patients shows that a score >1.6 correlates with advanced fibrosis.